2022
DOI: 10.1093/biosci/biac064
|View full text |Cite
|
Sign up to set email alerts
|

Culture and Quality Matter in Building Effective Mentorship Relationships with Native STEM Scholars

Abstract: Native peoples (Native American, Alaskan Native, Native Hawaiian) are underrepresented in academia; they represent 2% of the US population but 0.01% of enrolled undergraduate students. Native peoples share the experiences of colonization and forced assimilation, resulting in the loss of ancestral knowledge, language, and cultural identity. Recognizing history and the literature on social integration and mentorship, we followed 100 Native science and engineering scholars across a year of participation in the hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 31 publications
1
11
1
Order By: Relevance
“…Meta-analytic findings indicate that mentoring support and relationship quality were exhibited small positive correlations with outcomes such as sense of belonging, learning, and persistence intentions (ρ range: |0.01| -|0.41|, median ρ = |0.22|; Eby et al, 2013). Consistent with the meta-analytic findings, recent research on mentoring in college STEM contexts found that high-quality mentoring support promoted small-to-moderate gains in STEM belonging, identity, interest, self-efficacy, persistence intentions, values, and well-being (Estrada et al, 2022;Saw et al, 2022;Du et al, 2023;Kuchynka et al, 2023). Furthermore, STEM undergraduates' psychological similarity with their faculty mentor has a moderate-to-strong positive association with relationship quality and mentor-mentee relationship satisfaction (Hernandez et al, 2017(Hernandez et al, , 2023Pedersen et al, 2022).…”
Section: Mentoring In College Stem Contextssupporting
confidence: 66%
“…Meta-analytic findings indicate that mentoring support and relationship quality were exhibited small positive correlations with outcomes such as sense of belonging, learning, and persistence intentions (ρ range: |0.01| -|0.41|, median ρ = |0.22|; Eby et al, 2013). Consistent with the meta-analytic findings, recent research on mentoring in college STEM contexts found that high-quality mentoring support promoted small-to-moderate gains in STEM belonging, identity, interest, self-efficacy, persistence intentions, values, and well-being (Estrada et al, 2022;Saw et al, 2022;Du et al, 2023;Kuchynka et al, 2023). Furthermore, STEM undergraduates' psychological similarity with their faculty mentor has a moderate-to-strong positive association with relationship quality and mentor-mentee relationship satisfaction (Hernandez et al, 2017(Hernandez et al, , 2023Pedersen et al, 2022).…”
Section: Mentoring In College Stem Contextssupporting
confidence: 66%
“…This finding indicates that the TAD framework might benefit from explicit attention to interpersonal match between mentors and mentees because mentors who perceive their mentees as similar to them may provide more guidance and resources that support their mentees’ competence development. Indeed, prior research has shown the importance of deep‐level similarity, meaning shared values and culture, for promoting high‐quality STEM mentoring relationships 17–19 …”
Section: Resultsmentioning
confidence: 99%
“…Indeed, prior research has shown the importance of deep-level similarity, meaning shared values and culture, for promoting high-quality STEM mentoring relationships. [17][18][19]…”
Section: Undergraduate Researcher Characteristicsmentioning
confidence: 99%
“…Additionally, these cultural teachings strengthen faith and hope, and help students remain persistent no matter the challenge, just as ancestors would expect. In fact, the ability to enhance their own cultural identity and self-awareness becomes both a source and an indicator of their strength and success (Estrada et al, 2022; Wilkie, 2020). Historical attempts at erasure, invalidation, and extinction of American Indian culture necessitate faculty awareness of both the impact of historical events and the importance of recognizing and highlighting culturally derived student strengths, protective factors, and indicators of student success.…”
Section: Faculty and Institutional Attributes Of Culturally Safe Ment...mentioning
confidence: 99%